BIODIVERSITY OF ARACEAE IN MALABAR CITY FOREST, MALANG CITY, EAST JAVA - Aulia Azahra, Rahmania; Syamsuddin, Imam; Asyaun Niqris, Adelliana; Relia Fitrah, Aura; Nadia, Intan; Setyoningrum, Nadia; Chairani Fatimah, Nina; Fardhani, Indra; Qomaliyah, Eka Nurul (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
Indonesia, located on the equator with over 17,000 islands, is among the world's most biodiverse countries. Malabar City Forest in Malang serves as both a green space and a habitat for various plant species, including members of the Araceae family. Despite their roles in microclimate regulation, air purification, and soil stabilization, Araceae diversity in urban areas remains underexplored. This study aimed to identify and document Araceae species in Malabar City Forest and assess their ecological roles. Using an exploratory survey and cruise sampling, species were recorded based on their morphology. Field data were collected through direct observation aided by smartphone-based identification tools and validated with online taxonomic resources and literatures. Seven species were identified: Dieffenbachia seguine (Jacq.) Schott, Epipremnum aureum (Linden & André) G.S Bunting, Alocasia plumbea Van Houtte, Syngonium angustatum Schott, Syngonium podophyllum Schott, Epipremnum pinnatum (L.) Engl., and Typhonium trilobatum Schott, representing six genera. Their presence highlights adaptability to urban environments and potential as bioindicators. Future research should assess their ecological resilience and interactions. Local conservation through education, labeling, and habitat preservation can support biodiversity awareness and sustainable urban planning.